Analysis Effectiveness Program Apprenticeship for Synchronization Link and Match College Tall with World Industry - Muslih Muslih (Inspire Global Insight Journal, 2026)
This research aimed to find industrial needs about students' abilities and skills during apprenticeship at company. This research is descriptive quantitative, which is using questionnaires to collect data from the respondents. The results showed that, the apprentice program had be effective enough, but there were still constraints that faced by student. The constraints were soft skills, communication, interaction, adaptation, discipline and computer skills. The most useful competence were computer skills and soft skills to connect to the people.